Mechanistic Study on the Alleviation of Endometritis in Mice Through Inhibition of NF-κB and MAPK Signaling Pathways by Berberine and Carvacrol - Xiaoshan Liang; Yabo Wang; Tianyi Li; Peilong Li; Guojun Jiang (Microorganisms)
Berberine and carvacrol have demonstrated anti-inflammatory effects; however, their therapeutic potential in endometritis remains unclear. (Aims) This study aimed to examine the anti-inflammatory properties of berberine and carvacrol in a murine model of endometritis, with a focus on the underlying molecular mechanisms. (Main methods) The model was established via vaginal instillation of 0.1 mL of a mixture containing Escherichia coli, Staphylococcus aureus, and Group B Streptococcus, followed by treatment with 0.1 mL of berberine (4 mg/mL) and carvacrol (0.125 mg/mL) six days post-infection. All mice were euthanized on day 13, and uterine tissues were collected for subsequent analyses. (Key findings) Treatment with berberine and carvacrol significantly reduced tissue injury associated with endometritis, decreased mRNA expression of TLR2 and TLR4 (p < 0.01), and inhibited the phosphorylation of NF-κB and MAPK pathway-associated proteins, as well as the mRNA expression and levels of pro-inflammatory cytokines. (Significance) Berberine and carvacrol exhibit significant therapeutic effects against bacterial-induced endometritis by reducing TLR2 and TLR4 expression, inhibiting NF-κB and MAPK pathway activation, and decreasing pro-inflammatory cytokine production, thus demonstrating robust anti-inflammatory activity.